STUDY OF COMMUNITY PERCEPTION OF VILLAGE GOVERNMENT REGULATIONS IN PROTECTING THE MANGROVE FOREST AREA OF AIMOLI VILLAGE - Paulus Edison Plaimo; Imanuel Lamma Wabang (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
The purpose of this research is to know the perception of aimoli village community towards the protection of mangrove tourism area of Aimoli Village by issuing Village Regulations. Because the positive impact received for the lives of the people of Aimoli Village is very large. Where in addition to providing environmental services related to providing aquatic resources, on the other hand, also provides economic improvement benefits from tourism aspects. But community activities in mangrove tourism areas often occur by not being environmentally friendly such as felling mangrove trees to be used as building materials or firewood. This research uses likert scale method. According to the results of the study; (1) Public perception on the protection of mangrove areas requires perdes? category Strongly agree 3.57%; Agree 32.1%; Neutral 32.1%; Disagree 7.1%; Strongly Disagree 25%. The interval value is 79 in the Medium category; (2) Public perception of sanctions for the perpetrators of mangrove tourism in Aimoli Village is as follows: Category Strongly Agreed 53.6%; Agree 35.7%; Neutral 0.0%; Disagree 10.7%; and the category strongly disagrees 0.0%. The interval value of 121, with a very high category, in the majority gives an answer to sanctions to the perpetrators of the destruction of mangrove forest areas.